The Syndicate [videorecording (DVD)] : all or nothing - Andrews, Anthony, 1948-; Krige, Alice, 1954-; Henry, Lenny (Acorn, 2016)
The once-impressive Hazelwood Manor has been in the family of Lord Hazelwood since the eighteenth century. There used to be more than 30 staff at the house, but now, with a mounting debt of 6.5 million, only five remain since Lord and Lady Hazelwood were forced to let the others go. With the future of Hazelwood in question and their jobs on the line, the unthinkable happens, the staff wins the lottery!